Study on fouling index of humic acid removal by polyethersulfone ultrafiltration membrane - Saw, Wen Qi (2014)
Over the past few decades, membrane processes has received overwhelming attention worldwide in drinkable water production offering advantages such as compact module, lower energy consumption, environmental friendliness and high quality of water product which is independently on the fluctuations in feed quality. Among those methods, ultrafiltration membrane process has receives the most attention publicly. Ultrafiltration (UF) membrane technology is a low pressure driven membrane separation process aimed to recover water from a saline solution pressurized to a point greater than the osmotic pressure of the solution. In essence, this membrane can filters viruses and microorganisms under low applied pressure and create high permeate flux. These will save a lot of cost as the process only consume little energy. However, for this successful application, the major critical issue is fouling. The major foulants come from the natural organic matters (NOM) where it is mainly in the river water. This NOM consists of humic acid where it is the main fouling factor to the UF membrane. Humic acid will cause pore blockage or cake formation on the membrane that will further decrease the permeate flux of the filtered water. In spite of that, there are also many fouling factor that increase the fouling index of humic acid on UF membrane such as trans-membrane pressure and pH of the feed solution which represent the feed characteristic and the operation parameter that will probably contribute to the fouling index of the membrane. Therefore, a study will be done on parameters, pH of the feed solution and addition of calcium ion in order to investigate the fouling index of humic acid on membrane. The experiments start with the pure water permeability test with different pressure. Then, the fouling experiments wil start with filtration of humic acid solution with different pH, 3, 6 and 9. The fouling index, flux and solute rejection has been studied. The result obtained showed that permeate flux was lower whenever the pH of humic acid solution was lowered due to fouling in contraty the flux was higher when the pH is high. This phenomenon showed that membrane is easier to foul when the pH is low. Besides that, since the flux was decrease, which means the membrane was fouled. Hence, the fouling index of the membrane was increased when pH was low while decreased when the pH was high. Lastly, the solute rejection is related with the fouling of the membrane. When the membrane was fouled under low pH, the rejection of the membrane was increased because the membrane pore was partially block. Adversely, the rejection of the membrane is lower under high pH as the membrane was less fouled. To achieve the desired volume, longer filtration time was taken